HOS Tjokroaminoto: Guru Bangsa dan Pelopor Pergerakan Nasional Indonesia - Mulyanto Mulyanto; Melani Melani; Ratna Jauhara; Sudiarto Sudiarto; Abu Husein Ibrahim (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the role and thought of H.O.S. Tjokroaminoto in shaping national consciousness and producing leading figures of the Indonesian national movement. The core problem of the research focuses on how Tjokroaminoto’s leadership, ideas, and political educational practices contributed to the formation of Indonesian nationalism. The purpose of this study is to explain and analyze Tjokroaminoto’s position as a Teacher of the Nation and a central actor in the national movement. This research employs a library research method through a critical review of relevant books, journal articles, and scholarly works as primary and secondary data sources. The findings indicate that Tjokroaminoto played a strategic role through consciousness-based education, moral exemplarity, and organizational leadership. The study concludes that political education constituted a fundamental foundation in the emergence of Indonesian national consciousness.